Kaderisasi pemuda buddhis di Desa Tempuran Kabupaten Temanggung melalui Partisipasi Kegiatan Keagamaan sebagai Upaya Mempertahankan Saddhā - Metta Puspita Dewi (Jurnal Pelita Dharma, 2018)
The regeneration can be defined as the process of preparing the next generation for organization the sustainability. Religious leaders, religious teachers and parents as subjects need to motivate the youth as the regeneration’s object in maintaining the faith. The faith (saddhā) on the Buddha Dhamma is derived from the verification process (ehipassiko) and based on wisdom (paññā) rather than just believing.This study used a qualitative approach with observation, interview and documentation techniques.The results show that the pattern of regeneration built by parents and religious leaders as the regeneration subject. The regeneration applied to all Buddhist youth in order to have faith in the Buddha Dhamma. The purpose of regeneration is to maintain the Buddhism existence in the Tempuran Village. The method of human resources development by religious leaders as the subject regeneration and youth is conducted through training and development with the on the job training techniques. The youth as the object of regeneration are trained to lead the puja bhakti (Buddhist Ceremony), master of ceremony, visit and be a delegation on PATRIA. Kaderisasi diartikan sebagai proses mempersiapkan generasi penerus untuk keberlangsungan organisasi. Tokoh agama, guru agama, dan orang tua sebagai subjek perlu memotivasi pemuda sebagai objek kader dalam mempertahankan keyakinan. Keyakinan (saddhā) terhadap Buddha Dhamma dibangun dari proses verifikasi (ehipassiko) dan dilandasi kebijaksanaan (paññā), bukan sekadar kepercayaan membuta. Penelitian  ini menggunakan jenis penelitian kualitatif studi kasus dengan menggunakan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian menampilkan pola kaderisasi yang dibangun oleh orang tua dan tokoh agama sebagai subjek kaderisasi. Kaderisasi diberlakukan kepada semua pemuda Buddhis agar memiliki keyakinan terhadap Buddha Dhamma. Tujuan kaderisasi untuk mempertahankan eksistensi Agama Buddha di Desa Tempuran. Metode pengembangan sumber daya manusia oleh tokoh agama sebagai subjek kader diupayakan melalui pelatihan  dan partisipasi. Para pemuda sebagai objek kaderisasi mendapatkan tugas memimpin puja bakti, pembawa acara, anjangsana serta menjadi delegasi pada kegiatan Pemuda Theravada Indonesia (Patria).